The Effect of Health Belief Model-based Health Education on Self-Management Behavior in Preventing Stroke Among Hypertension Patients - Dika Ratna Sari; Yurike Septianingrum; Andikawati Fitriasari; M. Shodiq (Institut Kesehatan YARSI Mataram, 2026)
This study examined the effect of Health Belief Model (HBM)–based health education delivered through an e-booklet on self-management behavior among patients with hypertension. A quasi-experimental, non-randomized control-group pretest–posttest study was conducted at a primary healthcare center in Surabaya, Indonesia. Forty patients with grade II hypertension were recruited through purposive sampling and allocated to intervention (n = 20) and control (n = 20) groups. The intervention group received six online educational sessions over three weeks, while the control group received routine leaflet-based education. Self-management was measured using the 40-item Hypertension Self-Management Behaviour Questionnaire. Data were analyzed using Wilcoxon signed-rank and Mann–Whitney U tests. The intervention group demonstrated significant improvements in self-integration, self-regulation, interaction with health workers, self-monitoring, and medication adherence (all p = 0.001), whereas the control group showed no significant changes. Post-intervention scores differed significantly between groups across all domains (p = 0.002, 0.025, 0.019, 0.004, and 0.022, respectively). HBM-based education through an e-booklet was associated with improved hypertension self-management and may complement routine education in primary healthcare.